A Multi Echelon Mixed Integer Linear Programming Model of a Close Loop Supply Chain Network Design. (2018) - Pant, Kamlesh; A.R.Singh,; Pandey, Utkarsh; Purohit, Rajesh
Abstract: For the environment purpose, manager include efficient recovery system in supply chains. This recovery system has given birth to the concept of closed loop supply chain (CLSC). In this paper, an attempt has been made to design of CLSC network for minimization of total cost. For this purpose, four echelons (suppliers, manufacturer, distribution center and customer) in forward chain and six echelons (collection center, repair center, dismantling center, decomposition center, disposal site and secondary market) in backward chain have been considered. Further, a mixed integer linear programming model is developed to tackle the CLSC design problem. For the validity of the model, a numerical example has been considered which solved by using Branch and Bound method.